2019
DOI: 10.3389/fendo.2019.00113
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Issues in Long-Term Survivors of Testicular Cancer

Abstract: Testicular cancer is the most frequent tumor in young males aged 15–39 years. As cure rates are currently around 90%, the prevalence of survivors is increasing. However, a disease-free condition does not necessarily correspond to a life free of physical and psychosocial health problems. The aim of this review was to explore psychosocial morbidity among testicular cancer survivors. A literature search was conducted in three electronic databases (PubMed, Medline, and Embase). The results of the search on cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 113 publications
1
49
0
1
Order By: Relevance
“…They may also worry about dealing with common life challenges that young and middle-aged men already face (eg, establishing a family and career) in combination with the body image, sexuality and fertility issues that come with TC. [5][6][7] More efforts are needed to determine patient characteristics that increase the risk of higher anxiety scores. One small fair-quality study found anxiety was associated with sexual confidence and functioning, and cognitiveemotional regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They may also worry about dealing with common life challenges that young and middle-aged men already face (eg, establishing a family and career) in combination with the body image, sexuality and fertility issues that come with TC. [5][6][7] More efforts are needed to determine patient characteristics that increase the risk of higher anxiety scores. One small fair-quality study found anxiety was associated with sexual confidence and functioning, and cognitiveemotional regulation.…”
Section: Discussionmentioning
confidence: 99%
“…1,4 The burden and risk of treatment side effects are generally higher for those who received chemotherapy. 4 TC survivors are often concerned about sexuality, fertility, body image and male identity [5][6][7] which can impact survivor's quality of life. For instance, a recent study found that at least 26% of TC patients experienced sexual dysfunction and 28% had significant reproductive concerns.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar vein, Ryan and Hoyt [13] reported that men's adjustment following treatment for TC proved to be a challenge and therefore they found themselves unable to successfully navigate into adulthood and experienced greater functional challenges in later life. Such problems, including individual health, sexual relationships and work problems, were found by Schepisi et al [14] to affect several important aspects of survival and significantly influence the QoL of long-term survivors. The authors concluded that to better understand the impact of TC on QoL, sociocultural differences in sexuality, masculinity and fertility must be taken into consideration.…”
Section: Introductionmentioning
confidence: 96%
“…In TC survivors, platinum concentrations correlated with the cisplatin dose used during therapy have been associated with neurotoxicity and other long-term adverse consequences ( 101 103 ). Within this context, it is important to underline the importance of the effects of treatment on a physical level ( 104 ), including erectile dysfunction ( 105 ), reduction in sexual activity ( 106 ), and loss of desire ( 107 ). In particular, a correlation between previous chemoradiotherapy and radiotherapy and the risk of erectile dysfunction was recently confirmed by a Danish study on a cohort of 2,260 TC survivors ( 108 ).…”
Section: Stress-induced Immunosenescence In Testicular Cancer Survivomentioning
confidence: 99%